2011
DOI: 10.1111/j.1532-5415.2011.03534.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Structure and Function and Dependency in the Oldest Old

Abstract: In this age-homogenous cohort of the oldest old, high LVMI and LAVI and indices of systolic but not diastolic function as assessed according to Doppler were associated with limitations in ADLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
0
13
1
2
Order By: Relevance
“…The eGFR was calculated based on the Cockroft-Gault equation for Chinese individual: Creatinine Clearance (Ccr) = ((140 − age) × body weight)/(serum creatinine × 72) × (0.85, if female) [18]. …”
Section: Methodsmentioning
confidence: 99%
“…The eGFR was calculated based on the Cockroft-Gault equation for Chinese individual: Creatinine Clearance (Ccr) = ((140 − age) × body weight)/(serum creatinine × 72) × (0.85, if female) [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Due to the association with lower scores on the CS-PFP-10, increased LAVI could potentially function as a marker of increased risk of loss of independence in individuals over the age of 65 (Cress & Meyer, 2003). Recently, Leibowitz et al (2011) reported that 85- and 86-year-olds requiring assistance with at least one activity of daily living (dependent) were likely to have higher LAVI and LV mass index, along with a lower EF, than independent subjects of the same age. Consistent with the results of the current study, no Doppler measures of diastolic function differed between the dependent and independent groups.…”
Section: Discussionmentioning
confidence: 99%
“…The discipline of nursing does not specifically use the term optimum function. The nursing profession does use functional status, which pertains to an individual's physical, psychosocial, cognitive, spiritual, and physiological state (Leibowitz et al, 2011;Leidy, 1994;Pihl, Fridlund, & Martensson, 2011;Ski, Thompson, Hare, Stewart, & Watson, 2012). The discipline of nursing utilizes the term functional status to encompass and measure performance of an individual's ability to meet his/her needs, complete expected tasks, and sustain healthy living and comfort (Leidy, 1994;Wang, 2004).…”
Section: Disciplines' Use Of Optimum Functionmentioning
confidence: 99%